EFEKTIVITAS REHABILITASI DALAM TERHADAP PENYALAHGUNAAN NARKOTIKA SEBAGAI UPAYA DEPENALISASI - Aras Firdaus; Wahyu Simon Tampubolon; Desy Kartika Caronina Sitepu (Jurnal Ilmiah Advokasi, 2022)
Drug abuse has become a national and international problem. Drug abuse can cause physical and mental damage. As for victims of users or addicts, the government has made efforts to reduce the adverse effects of drug use by providing rehabilitation facilities, both medically and socially. This is done so that victims of drug users can recover, become productive human beings, able to work to meet the needs of life and their families, and become the next generation of the nation in the future. The problem in this research, namely how is the regulation of laws and regulations regarding the legal protection of victims of narcotics crime in Indonesia? How do law enforcement officers deal with narcotics crimes? The research method used in this research is normative juridical. This research is descriptive analytical, the purpose of this research is to obtain a detailed and systematic picture to answer the problems to be studied. The results of the study show that the effectiveness of regulations regarding rehabilitation by victims of narcotics crimes does not always run well. The understanding of some law enforcement officers in interpreting the law regarding rehabilitation is not the same so that among law enforcers there are multiple interpretations in interpreting the law. Thus, some law enforcement officers make victims as perpetrators of narcotics crimes. So in the future, law enforcement will prioritize the rights of victims of narcotics crimes for legal certainty and legal justice.Keywords: Rehabilitation, Law Enforcement, Narcotics